2015
DOI: 10.1186/s40163-015-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

How victim age affects the context and timing of child sexual abuse: applying the routine activities approach to the first sexual abuse incident

Abstract: The aim of this study was to examine from the routine activities approach how victim age might help to explain the timing, context and nature of offenders' first known contact sexual abuse incident. One-hundred adult male child sexual abusers (M = 45.8 years, SD = 12.2; range = 20-84) were surveyed about the first time they had sexual contact with a child. Afternoon and early evening (between 3 pm and 9 pm) was the most common time in which sexual contact first occurred. Most incidents occurred in a home. Two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…Using a sample of 350 Canadian sexual homicide cases, the authors examine victim selection from a routine activity perspective using CRAVED. McKillop et al (2015) also apply the routine activity approach to investigate contextual risk factors in offenders' first known child sexual abuse incident. Focusing particularly on how victim age influences the timing, context and nature of the first abuse incident, they surveyed 100 adult males convicted of contact sexual offences with children about situational characteristics of these incidents.…”
mentioning
confidence: 99%
“…Using a sample of 350 Canadian sexual homicide cases, the authors examine victim selection from a routine activity perspective using CRAVED. McKillop et al (2015) also apply the routine activity approach to investigate contextual risk factors in offenders' first known child sexual abuse incident. Focusing particularly on how victim age influences the timing, context and nature of the first abuse incident, they surveyed 100 adult males convicted of contact sexual offences with children about situational characteristics of these incidents.…”
mentioning
confidence: 99%
“…As previously mentioned, the majority of sex crime studies have been conducted to develop effective and practical prevention models. As a part of the preventative models, increasing guardianship and/or target hardening have been suggested (McKillop, Brown, Wortley, & Smallbone, 2015;Terry & Freilich, 2012). By implementing such strategies, motivated offenders are supposed to be discouraged to continually carry out their sexual behaviors against children.…”
Section: Overview Of Sexual Violence Studiesmentioning
confidence: 99%
“…Hence, child molesters can take advantage of opportunities arising in the context of daily activities while performing caregiver duties (McKillop et al, 2015), and they often intentionally place themselves in a position where they can meet children and have opportunity to interact with children in an unsupervised way (Bagley, Wood, & Young, 1994;Finkelhor & Williams, 1988;Quayle & Taylor, 2001). Tewksbury and Mustaine (2003) revealed that lifestyle behaviors and characteristics could serve better as predictors of crime-commission and target selection processes than the demographics of the involved in sex crimes among college students.…”
Section: Victim Vulnerabilitymentioning
confidence: 99%
See 2 more Smart Citations